The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fped.2020.00260
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics Alterations in Critically Ill Pediatric Patients on Extracorporeal Membrane Oxygenation: A Systematic Review

Abstract: Objectives: This study aimed to identify alterations in pharmacokinetics in children on extracorporeal membrane oxygenation (ECMO), identify knowledge gaps, and inform future pharmacology studies. Data Sources: We systematically searched the databases MEDLINE, CINAHL, and Embase from earliest publication until November 2018 using a controlled vocabulary and keywords related to "ECMO" and "pharmacokinetics," "pharmacology," "drug disposition," "dosing," and "pediatrics." Study Selection: Inclusion criteria were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Despite the known effect of ECMO on the PK of some drugs ( Sutiman et al, 2020 ), the measurements obtained from three patients (5%) on ECMO were included in the analysis. The decision to include these patients in the analysis was made after ensuring that the PEs obtained for these subjects were not different from the average PE estimated for the respective model.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the known effect of ECMO on the PK of some drugs ( Sutiman et al, 2020 ), the measurements obtained from three patients (5%) on ECMO were included in the analysis. The decision to include these patients in the analysis was made after ensuring that the PEs obtained for these subjects were not different from the average PE estimated for the respective model.…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, antibiotic use is high in ECMO patients [117]. It has been suggested that ECMO may lead to additional PK alterations during antibiotic therapy in critically ill patients [117][118][119].…”
Section: Extracorporeal Organ Support Systems 421 Extracorporeal Membrane Oxygenationmentioning
confidence: 99%
“…The potential impact of ECMO on antibiotic PK can be related to the direct interaction of the antibiotic with the ECMO circuit (e.g., adsorption to the tubing or oxygenator) [117][118][119]. Ex vivo experiments revealed that drugs with a higher degree of lipophilicity and drugs with high plasma protein binding are most at risk of sequestration within the ECMO circuit [118,120].…”
Section: Extracorporeal Organ Support Systems 421 Extracorporeal Membrane Oxygenationmentioning
confidence: 99%
See 2 more Smart Citations